Topical administration of deep sea shark liver oil (desslotm) inhibited mmp-1 expression in rat’s skin exposed to ultraviolet-B - Bunge Dianmentari; Gede Ngurah Indraguna Pinatih; Anak Agung Gede Putra Wiraguna (Fakultas Kedokteran Universitas Udayana, 2020)
Introduction: Squalene is one of strong antioxidants that can inhibit aging proses. However, its effect on the skin aging is still understudied. Therefore, the purpose of this study was to assess the efficacy of topical administration of Deep Sea Shark Liver Oil toward MMP-1 expression in Wistar rat’s (Rattus Norvegicus) skin exposed to UVB. Methods: An experimental randomized post-test only control group study was conducted using a total of 36 rats Wistar rats were used which were divided into 2 groups. The control group received placebo solution while the treatment group was treated by Deep Sea Shark Liver Oil solution. All groups were exposed to UVB with a total dose of 840 mJ/cm² for 4 weeks. Biopsy was conducted for skin sample collection for the examination expression of MMP-1. Results: Immunohistochemistry evaluation showed that the dermal MMP-1 expression in the control group was higher than in control group. According to the percentage of expression analysis, the mean of MMP-1 expression in control group were significantly higher (29.53%) compared to the treatment group (9.72%) (p=0.001). Conclusion: It can be concluded that the topical administration of Deep Sea Shark Liver Oil solution inhibited the expression of MMP-1 in rat’s skin exposed to UVB.